2008
DOI: 10.2466/pms.107.2.607-617
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Translational and Rotational Motions and Display Polarity on Visual Performance

Abstract: This study investigated effects of both translational and rotational motion and display polarity on a visual identification task. Three different motion types--heave, roll, and pitch--were compared with the static (no motion) condition. The visual task was presented on two display polarities, black-on-white and white-on-black. The experiment was a 4 (motion conditions) x 2 (display polarities) within-subjects design with eight subjects (six men and two women; M age = 25.6 yr., SD = 3.2). The dependent variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The other is negative polarity which refers to the condition where light characters are displayed on a dark background. Generally, positive display polarity reduces optical distortion and enhances contrast sensitivity, depth of field, speed of lens accommodation, visual discrimination, and visual identification of motion (Bauer and Cavonius 1980, Feng, et al 2008, Mayr and Buchner 2010. Positive polarity displays were rated higher than negative ones when visual acuity and luminance contrast were considered important for a task (Bergqvist 1984), and when pupil and lens accommodation were tested (Saito et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The other is negative polarity which refers to the condition where light characters are displayed on a dark background. Generally, positive display polarity reduces optical distortion and enhances contrast sensitivity, depth of field, speed of lens accommodation, visual discrimination, and visual identification of motion (Bauer and Cavonius 1980, Feng, et al 2008, Mayr and Buchner 2010. Positive polarity displays were rated higher than negative ones when visual acuity and luminance contrast were considered important for a task (Bergqvist 1984), and when pupil and lens accommodation were tested (Saito et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this categorisation, the colour combinations that could yield better task performance in visual discrimination were found to belong to the category of negative polarity (e.g., yellow on blue). Nevertheless, some research has found that positive polarity outperformed negative polarity in enhancing visual discrimination, identification, and perceived comfort (Bauer et al., 1980; Nishiyama, 1990; Snyder et al., 1990; Taptagaporn and Saito, 1990; Saito et al., 1993; Sanders and McCormick, 1993; Shieh and Lin, 2000; Wang et al., 2003; Chan and Lee, 2005; Feng et al., 2008; Mayr and Buchner, 2010; Tsang et al., 2012). For example, Shieh and Lin (2000) used a visual identification task to investigate 12 colour combinations from four colours (yellow, blue, red, and purple), half with negative polarity and half with positive polarity.…”
Section: Introductionmentioning
confidence: 99%
“…Visual search performance has been reported to be aff ected by target motion (Feng, Tseng, Chao, & Lin, 2008), target diffi culty (Chan & Tang, 2007), and eye movements (Rayner, 2009); and has been shown to be highly correlated with visual lobe size (Courtney & Chan, 1986;Hong & Drury, 2002;Chan & So, 2006). Visual lobe size generally refers to the area of a visual lobe.…”
mentioning
confidence: 98%
“…Recent studies on visual inspection have included exploration of search strategies in aircraft inspection, microchip inspection in the electronics industry, and military target acquisition (Gramopadhye, Drury, Jiang, & Screenivasan, 2002;Liang, 2008). Visual search performance has been reported to be aff ected by target motion (Feng, Tseng, Chao, & Lin, 2008), target diffi culty (Chan & Tang, 2007), and eye movements (Rayner, 2009); and has been shown to be highly correlated with visual lobe size (Courtney & Chan, 1986;Hong & Drury, 2002;Chan & So, 2006). Visual lobe size generally refers to the area of a visual lobe.…”
mentioning
confidence: 99%